Breakdown of gametophytic self‐incompatibility in subdivided populations. (2nd January 2020) - Brom, Thomas; Castric, Vincent; Billiard, Sylvain
Abstract: In many hermaphroditic flowering plants, self‐fertilization is prevented by self‐incompatibility (SI), often controlled by a single locus, the S‐locus. In single isolated populations, the maintenance of SI depends chiefly on inbreeding depression and the number of SI alleles at the S‐locus. In subdivided populations, however, population subdivision has complicated effects on both the number of SI alleles and the level of inbreeding depression, rendering the maintenance of SI difficult to predict. Here, we explore the conditions for the invasion of a self‐compatible mutant in a structured population. We find that the maintenance of SI is strongly compromised when a population becomes subdivided. We show that this effect is mainly caused by the decrease in the local diversity of SI alleles rather than by a change in the dynamics of inbreeding depression. Strikingly, we also find that the diversity of SI alleles at the whole population level is a poor predictor of the maintenance of SI. We discuss the implications of our results for the interpretation of empirical data on the loss of SI in natural populations.